The identity trade : selling privacy and reputation online - Draper, Nora A. (Critical cultural communication., 2019)
"The successes and failures of an industry that claims to protect and promote our online identities What does privacy mean in the digital era? As technology increasingly blurs the boundary between public and private, questions about who controls our data become harder and harder to answer. Our every web view, click, and online purchase can be sold to anyone to store and use as they wish. At the same time, our online reputation has become an important part of our identity--a form of cultural currency. The Identity Trade examines the relationship between online visibility and privacy, and the politics of identity and self-presentation in the digital age. In doing so, Nora Draper looks at the revealing two-decade history of efforts by the consumer privacy industry to give individuals control over their digital image through the sale of privacy protection and reputation management as a service. Through in-depth interviews with industry experts, as well as analysis of media coverage, promotional materials, and government policies, Draper examines how companies have turned the protection and promotion of digital information into a business. Along the way, she also provides insight into how these companies have responded to and shaped the ways we think about image and reputation in the digital age. Tracking the successes and failures of companies claiming to control our digital ephemera, Draper takes us inside an industry that has commodified strategies of information control. This book is a discerning overview of the debate around who controls our data, who buys and sells it, and the consequences of treating privacy as a consumer good."--Provided by publisher